A 15-mW fully integrated I - Leenaerts, D.M.W (IEEE Journal of solid state circuits)
A low-power fully integrated synthesizer for Bluetooth applications is presented. The circuit with quadrature output signals at 2.45 GHz and 15-mW power dissipation has been designed in a digital 0.18-μm CMOS process with 1.8-V supply voltage. The only external component is a 64-MHz crystal. Measurements have been performed on packaged samples mounted on an FR-4 board and show that the Bluetooth requirements are met. The measured phase noise is below -120 dBc/Hz at 3-MHz offset, and the resulting residual frequency modulation is 7.4-kHz rms. The tuning range consists of an analog and digital tuning mechanism, resulting in more than 15% overall tuning range.